Non-suicidal self-injury in adolescents and young adults with type 1 diabetes: clinical characteristics from a German diabetes-patient registry (DPV). (March 2021) - Eckert, Alexander; Domhardt, Matthias; Reinauer, Christina; Berger, Gabriele; Galler, Angela; Böckmann, Andreas; Henn, Martina; Haak, Thomas; Holl, Reinhard W.
Highlights: First study to address NSSI in patients with T1D NSSI is related to poor metabolic control, higher daily insulin dose, more frequent DKA and hospitalisation in adolescents and young adults with T1D 81% of patients with NSSI documented in the DPV registry were female and the effects on diabetes-related outcomes were greater in female than in male patients Abstract: The aim was to examine the relations between non-suicidal self-injury (NSSI) and clinical parameters as well as other psychiatric comorbidities in adolescents and young adults with type 1 diabetes mellitus (T1D). Patients aged 8-<=25 years with T1D and documented NSSI from the DPV database ( n =167) were compared to a control group with T1D without NSSI or other psychiatric comorbidities ( n =76, 050) using multivariable regression models, adjusted for demographics. Clinical diabetes-related outcomes (haemoglobin A1c (HbA1c), daily insulin dose, diabetic ketoacidosis (DKA), hypoglycaemia, number of hospital days, number of hospital admissions) were analysed. NSSI patients had significantly higher HbA1c (%): (+1.1 [0.8; 1.4]), higher daily insulin doses: (+0.08 (U/kg), [0.02; 0.13]), more DKA events per patient year: (+1.79 [1.22; 2.37]), more hospital days per patient year: (+0.25 [0.20; 0.29]) and more frequent hospital admissions per patient year: (+0.93 [0.79; 1.06]) compared to T1D patients without NSSI or other psychiatric comorbidities (differences of adjusted estimates [confidence interval]). This is the first study to investigate the association between NSSI and T1D. We revealed that NSSI is significantly related to diabetes outcomes in adolescent T1D patients. There should be an increased awareness for NSSI in the care for adolescents and young adults with T1D.